Achieving Entrepreneurial Renewal in Resource-Constrained SMEs through Digital Platforms: A Process-Oriented Model - Joddy Hernady; Brina Mariana (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Small and medium-sized enterprises are vital for economic growth but face challenges in adopting digital transformation due to limited resources. This study aims to explore how digital platforms enable these enterprises to achieve entrepreneurial renewal by developing a process-oriented model. Through a systematic literature review of 50 peer-reviewed studies published between 2010 and 2024, the research examines the role of digital platforms in fostering agility, experimentation, and capability-building across various sectors and regions. Findings reveal that internal drivers, such as entrepreneurial mindset and organizational learning, combined with external support from digital ecosystems and government policies, facilitate transformation. However, barriers like financial constraints, skill shortages, and infrastructural gaps hinder progress, particularly in rural or traditional enterprises. The study proposes a four-stage model Awareness and Motivation, Experimentation and Adoption, Reconfiguration and Scaling, and Strategic Renewal to guide enterprises through iterative transformation. This model emphasizes the dynamic interplay of internal capabilities and external opportunities. In conclusion, the framework offers a structured approach for small and medium-sized enterprises and policymakers to navigate digital transformation, addressing resource constraints and fostering sustainable innovation in diverse contexts.